Dynamic integration of public and private business processes - Lim, DeQiang. (2010)
The rapidly changing landscape of business has given rise to the need for enterprises to be quick and agile when it comes to business collaboration with other companies. Companies can no longer afford to have collaboration systems that are both rigid and costly in a rapidly changing world. They need to be able to collaborate quickly and effectively with new business partners “on-the-fly”.